2020
DOI: 10.1007/s00192-020-04241-4
|View full text |Cite
|
Sign up to set email alerts
|

Parturition mode recommendation and symptoms of pelvic floor disorders after obstetric anal sphincter injuries

Abstract: Introduction and hypothesis Our primary objective was to evaluate parturition mode (PM) recommendations following obstetric anal sphincter injuries (OASIs) and adherence to these recommendations and to evaluate recurrence of OASIs in women who had a subsequent vaginal delivery (VD). The hypothesis was that adherence to the PM recommendations leads to a reasonable OASI recurrence rate. Methods This was a retrospective observational cohort study of patients with previous OASIs between 2010 and 2016. After an out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…However, a follow-up examination focuses more on evaluating the symptoms, sequelae, and decisions regarding future deliveries. RCOG and ACOG recommend that if resources and facilities are available, women with OASIS should undergo endoanal ultrasonography and anal manometry to decide on future deliveries [13,14]. Unfortunately, endoanal ultrasonography and anal manometry are not convenient for postpartum women and it is usually conducted by colorectal surgeon, not a gynecologist.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, a follow-up examination focuses more on evaluating the symptoms, sequelae, and decisions regarding future deliveries. RCOG and ACOG recommend that if resources and facilities are available, women with OASIS should undergo endoanal ultrasonography and anal manometry to decide on future deliveries [13,14]. Unfortunately, endoanal ultrasonography and anal manometry are not convenient for postpartum women and it is usually conducted by colorectal surgeon, not a gynecologist.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, endoanal ultrasonography and anal manometry are not convenient for postpartum women and it is usually conducted by colorectal surgeon, not a gynecologist. A woman with the symptom of incontinence, severe anatomical defect on anal sphincter or levator ani avulsion, and low pressure of anal manometry is recommended to have an elective cesarean delivery [ 13 , 15 ]. Thus, emphasizing the importance of imaging examination on post-repair OASIS women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Several studies have shown that the extent of endosonographic anal sphincter defects is related to anal incontinence, [14][15][16] and one study aimed at evaluating parturition mode recommendations following obstetric anal sphincter injuries found that dyspareunia was more common in patients with residual external anal sphincter (EAS) defects. 17 This study aimed to determine the prevalence of postpartum anal sphincter defects using three-dimensional endoanal ultrasonography (3D-EAUS). The primary outcome was association of postpartum sonographic sphincter defects with symptoms of pelvic floor pain and dyspareunia.…”
Section: Introductionmentioning
confidence: 99%
“…Three dimensional endoanal ultrasound (3D‐EAUS) is a documented, well‐tolerated, and inexpensive method of evaluating damage to the anal sphincter and is considered the gold standard 13 . Several studies have shown that the extent of endosonographic anal sphincter defects is related to anal incontinence, 14–16 and one study aimed at evaluating parturition mode recommendations following obstetric anal sphincter injuries found that dyspareunia was more common in patients with residual external anal sphincter (EAS) defects 17 …”
Section: Introductionmentioning
confidence: 99%